CLINICAL PICTURE, DIAGNOSIS AND PREVENTION OF VENOUS THROMBOEMBOLIC COMPLICATIONS DURING PREGNANCY - S. V. Akinshina; A. D. Makatsariya; V. O. Bitsadz; M. D. Andreeva (IRBIS LLC, 2016)
Despite intensive research, venous thromboembolism still accounts for significant maternal mortality and morbidity. The article describes modern aspects of the pathogenesis, diagnosis, treatment, primary and secondary prevention of venous thromboembolism during pregnancy. Thrombophilia might be the essential pathogenetic mechanism of thromboembolism associated with pregnancy. Low molecular weight heparin (LMWH) is effective for prevention of recurrent thromboembolism and obstetric complications. Women with personal or family history of thromboembolism or with history of obstetric complications should be screened for thrombophilia.